Metal-coated hierarchical pore ZSM-5 catalyst for hydrocyclization isomerization of aviation kerosene carbon chain precursor substance
By loading metal components on the ZSM-5 support and forming a multi-stage pore structure and metal oxide coating, the existing ZSM-5 catalyst has been solved, and the hydrogenation and cyclization isomerization of the precursor substances of the aviation coal chain is achieved, and the catalyst stability and activity are significantly improved.
Patent Information
- Application Number
- CN202411811840.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-10
AI Technical Summary
When the existing ZSM-5 catalyst is used for the hydrogenation and cyclization and isomerization of precursor substances of aerospace coal carbon chain, the pores are small and the mass transfer effect is poor, making it difficult to meet the needs of industrial production.
The metal-clad multi-stage pore ZSM-5 catalyst is used to improve the activity and stability of the catalyst by supporting metal components such as iron, platinum and nickel on the ZSM-5 support, and forming a multi-stage pore structure and a metal oxide coating through hydrothermal and ion exchange steps.
It has achieved efficient hydrocyclization and isomerization of precursor substances of aviation coal chains at lower temperatures. The catalyst has high cyclization activity and isomerization activity, good stability, and is suitable for industrial production.
Smart Images

Figure CN119680625A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and specifically relates to a preparation method and application of a metal-coated multi-level porous ZSM-5 catalyst for hydrogenation cycloisomerization of aviation kerosene carbon chain precursors. Background Art
[0002] With the rapid development of the aviation industry, the demand for energy in modern aircraft is increasing day by day, and the requirements for the components of aviation kerosene are becoming increasingly stringent. Aviation fuel must not only have a high energy density to meet the needs of long-term high-load flight, but also must exhibit excellent combustion stability, anti-knock properties and low-temperature fluidity under a wide range of temperature and pressure conditions. However, the high proportion of straight-chain alkanes in traditional aviation kerosene has some shortcomings. Although straight-chain alkanes have a high energy density, their anti-knock properties are poor, and they are prone to cause knock in the engine, thereby reducing fuel efficiency and affecting engine safety. In addition, straight-chain alkanes have poor fluidity in low-temperature environments, and are prone to fuel condensation under severe cold conditions during high-altitude flight, which in turn affects the normal operation of the fuel supply system. Their thermal stability is also relatively low, and they are prone to form deposits under high-temperature conditions, shortening the engine life. Therefore, in the production process of aviation fuel, isomerizing straight-chain alkanes into branched alkanes or generating cycloalkanes through cyclization has become an effective optimization method.
[0003] Branched alkanes have higher anti-knock properties and more stable combustion performance due to their branched structure, while cycloalkanes provide good low-temperature fluidity and high thermal stability. These measures can not only improve the anti-knock performance of aviation fuel, but also significantly improve its low-temperature use characteristics and thermal stability, meet the strict requirements of modern aviation engines for fuel, and thus improve flight efficiency and safety. Therefore, it is of great significance to develop catalysts that can efficiently prepare branched alkanes and cyclize them to cycloalkanes at lower temperatures.
[0004] ZSM-5 has the advantages of abundant pores, good hydrothermal stability and easy regulation of acidity. By regulating the pore structure, metal loading and acidity, it is easy to achieve multiple functional development. Therefore, it has been widely used as a catalyst or catalyst carrier. However, when used for the cycloisomerization of aviation kerosene alkanes, due to the large reaction molecules, the original ZSM-5 has small pores and poor mass transfer effect, which is not suitable for industrial production. Some researchers choose to add strong alkaline substances and template agents to treat ZSM-5, such as sodium hydroxide, potassium hydroxide and tetrapropylammonium hydroxide, etc., to treat ZSM-5 into a hollow multi-level porous material MHS-Z5. The introduction of mesopores greatly enhances the mass transfer effect of macromolecules. Since MHS-Z5 itself is only acidic and does not have the effect of activating hydrogen, by loading precious metals or partial transition metals on the surface or inside of MHS-Z5, the loaded MHS-Z5 has both acidity and the ability to activate hydrogen, making it an excellent catalyst for the hydrogenation cycloisomerization of precursors with suitable carbon chain lengths. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a metal-coated multi-level porous ZSM-5 catalyst for the hydrogenation cycloisomerization of aviation kerosene carbon chain precursor substances in view of the deficiencies in the above-mentioned prior art.
[0006] A metal-coated multi-level porous ZSM-5 catalyst for hydrogenation cycloisomerization of aviation kerosene carbon chain precursor, the preparation method of which comprises the following steps:
[0007] Step 1, dissolving one or two or more of an iron salt, a platinum salt and a nickel salt in deionized water in proportion to obtain a mixed solution A;
[0008] The mass fraction of Fe in the iron salt is 1-5wt%, the mass fraction of Pt in the platinum salt is 1-5wt%, the mass fraction of Ni in the nickel salt is 1-5wt%, and the rest is deionized water.
[0009] The nickel salt is one of nickel nitrate, nickel acetate and nickel chloride, or a combination of two or more thereof; the iron salt is one of iron nitrate, iron chloride, iron nitrate, iron oxalate and iron acetate, or a combination of two or more thereof, preferably iron nitrate or iron chloride; the platinum salt is one of platinum chloride, chloroplatinic acid and platinum nitrate, or a combination of two or more thereof.
[0010] Step 2: Add the mixed solution A to the H-type ZSM-5, add a magnetic particle, and stir vigorously on a magnetic stirrer at room temperature until the compound is fully impregnated into the ZSM-5 carrier;
[0011] The immersion time is 3 to 10 hours, preferably 5 to 8 hours.
[0012] Step 3, drying and calcining the impregnated material to obtain supported metal oxide / ZSM-5;
[0013] The drying temperature is 80-120°C; the calcination temperature is 400-550°C, and the calcination time is 6 hours;
[0014] Step 4, adding tetrapropylammonium hydroxide and sodium hydroxide solution to the supported metal oxide / ZSM-5, stirring, hydrothermal, centrifuging, drying, and calcining to obtain a sodium-type metal oxide-coated multi-level porous catalyst metal oxide@MHS-Z5;
[0015] The mass fraction of tetrapropylammonium hydroxide is 25wt%, and the molar ratio of tetrapropylammonium hydroxide to sodium hydroxide is 1-12:1, preferably 1-8:1; the hydrothermal reaction temperature is 110-200°C, and the time is 48-96h; the filter cake drying temperature is 60-120°C; the calcination temperature is 500-700°C, the heating rate is 4-10°C / min, and the calcination time is 4-8h.
[0016] Step 5: Disperse the metal oxide @MHS-Z5 powder in an aqueous solution of ammonium chloride and stir to perform ion exchange.
[0017] After drying and calcination, H-type metal oxide@MHS-Z5 was obtained;
[0018] Each gram of metal oxide @MHS-Z5 powder is added to 30-60 ml of ammonium chloride solution;
[0019] The concentration of ammonium chloride is 0.5 to 2 M, the stirring time is 2 to 4 hours, and the ion exchange is repeated 2 to 3 times.
[0020] The drying temperature is 60-100°C, the calcination temperature is 300-600°C, and the calcination time is 4-7h.
[0021] Step 6: at 300℃~500℃, H 2 / Ar environment to reduce H-type metal oxide @MHS-Z5 to obtain reduced metal @MHS-Z5.
[0022] A metal-coated multi-level porous ZSM-5 catalyst for hydrogenation cycloisomerization of jet fuel carbon chain precursors, comprising a multi-level porous hollow ZSM-5 carrier and one or more metal components Fe, Ni or Pt. The contents of the metal components are 1 to 5 wt% Ni, 1 to 5 wt% Fe and 1 to 5 wt% Pt respectively. The specific surface area of the multi-level porous hollow ZSM-5 carrier is 402 to 440 m 2 / g, its pore volume is 0.43~0.21ml / g, and B acidity is 12~26mmol / g.
[0023] The metal-coated multi-level porous ZSM-5 catalyst is used for the hydrogenation cycloisomerization of aviation kerosene carbon chain precursors containing 10 to 15 carbon atoms, with the product cycloalkanes or isoalkanes being 30 to 50%, and the total of the product cycloalkanes and isoalkanes being 50 to 70%.
[0024] The advantages and beneficial effects of the present invention are:
[0025] (1) The jet fuel carbon chain precursor hydrogenation cyclization isomerization catalyst prepared by the present invention has high cyclization activity and isomerization activity and good catalytic stability.
[0026] (2) When the aviation kerosene carbon chain precursor hydrocycloisomerization catalyst prepared by the present invention is used for hydrocycloisomerization reaction, the reaction temperature is low and the cycloisomerization activity of the aviation kerosene long-chain alkanes can be maintained at a relatively low temperature.
[0027] (3) The method for preparing the catalyst for the hydrogenation cycloisomerization of the carbon chain precursor of aviation kerosene of the present invention has the advantages that the equipment is easily available during the production process, the reaction conditions are controllable, and the production efficiency is higher. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a comparison chart of the results of using the catalysts prepared in Examples 1-4 for hydrocycloisomerization reactions;
[0029] Figure 2 This is the TEM characterization image of the A4 catalyst prepared in Example 4;
[0030] Figure 3 This is a comparison chart of the results of using the catalysts prepared in Examples 5-8 for hydrocycloisomerization reactions;
[0031] Figure 4 This is the diffraction characterization diagram of the catalyst powder prepared in Examples 5-8;
[0032] Figure 5 This is a transmission electron microscopy scan of the B2 catalyst prepared in Example 6;
[0033] Figure 6 This is a comparison chart of the results of using the catalysts prepared in Examples 9-11 in hydrocycloisomerization reactions;
[0034] Figure 7 The diffraction characterization diagram of the catalyst powder prepared in Examples 9-11;
[0035] Figure 8 This is a transmission electron microscopy scan of the C3 catalyst prepared in Example 11;
[0036] Fig. 9This is a comparison chart of the products of hydrogenation of the catalysts prepared in Examples 3, 6, 11 and Comparative Example 1 under the same conditions. DETAILED DESCRIPTION
[0037] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0038] The technical solution of the present invention is further explained below in conjunction with specific embodiments, but is not intended to limit the protection scope of the present invention.
[0039] The raw material for the hydrocycloisomerization of jet fuel is an oxygen-containing precursor substance containing 10 to 15 carbon atoms. The synthesis method comprises the following steps:
[0040] (1) After mixing furfural and sodium levulinate solution, add an appropriate amount of alkaline solid oxide, and react under vigorous stirring;
[0041] The molar ratio of furfural to sodium levulinate is 0.5 to 2:1, preferably 0.8 to 1:1.
[0042] The basic solid oxide is calcium oxide, magnesium oxide or barium oxide, preferably magnesium oxide, as a catalyst, and the mass ratio of furfural to oxide is 2 to 3:1;
[0043] The reaction temperature is 60-90°C and the reaction time is 5-10 hours;
[0044] (2) After the reaction is completed, the magnesium oxide is rapidly cooled by water and separated by centrifugation or filtration;
[0045] (3) adding the filtrate dropwise into an excess of dilute hydrochloric acid to produce a large amount of precipitate;
[0046] (4) The mixture is allowed to stand at room temperature for 3 to 6 hours. A water-insoluble brown oily substance appears on the wall of the beaker. The clear liquid is transferred to another beaker and the oily substance on the wall of the beaker is dried at 30 to 50°C. The dried brown solid is collected, ground, dried and stored. This is the C15 precursor.
[0047] (5) refrigerating the clear liquid at low temperature, a large amount of yellow crystals precipitate on the wall of the cup, collecting the yellow crystals and drying them at low temperature;
[0048] The temperature of low-temperature refrigeration is 4-10℃, and the refrigeration time is 8-12 hours; the temperature of low-temperature drying is 40-60℃, and the drying time is 8-12 hours
[0049] (6) After the dried product is dissolved again in water, the low-temperature refrigeration and low-temperature drying in step (5) are repeated 1 to 3 times to wash the precipitate;
[0050] (7) After washing, the yellow product is ground and stored, which is the C10 precursor.
[0051] The present invention prepares a metal-coated multi-level porous ZSM-5 catalyst for hydrogenating and cycloisomerizing the above-mentioned precursor material.
[0052] Example 1
[0053] (1) A calculated amount of chloroplatinic acid (1 wt% Pt) was dissolved in deionized water and added to the hydrothermally synthesized or commercially purchased H-type ZSM-5;
[0054] (2) The mixture was stirred vigorously, stirred at room temperature for 6 h, and then impregnated into a ZSM-5 support;
[0055] (3) The impregnated material in step (2) was dried at 85°C and calcined at 500°C for 6 hours to obtain a supported catalyst PtO 2 / ZSM-5;
[0056] (4) Add the calculated amount of TPAOH (25 wt%):NaOH:H 2 O mass ratio of 1:0.024:5.157 was added to the PtO prepared in step (3) 2 / ZSM-5, after stirring, hydrothermal in an oven at 170°C for 72 hours, centrifuged and dried at 85°C for 12 hours, and calcined at 550°C for 6 hours to obtain a sodium-type metal oxide-coated multi-level porous catalyst PtO 2 @Na-MHS-Z5;
[0057] (5) PtO obtained in step (4) 2 @Na-MHS-Z5 powder was dispersed in a 1 mol / L aqueous solution of ammonium chloride, stirred vigorously at 60 °C for ion exchange, and repeated ion exchange for 3 times, dried at 85 °C for 12 h, and calcined at 550 °C for 6 h to obtain H-type PtO 2 @MHS-Z5;
[0058] (6) At 350°C, 5% H 2 / Ar environment to remove the PtO in step (5) 2 @MHS-Z5 was reduced for 4 h to obtain the reduced cycloisomerization catalyst Pt@MHS-Z5, in which the mass fraction of active metal Pt was 1%, and was named catalyst A1.
[0059] The C10 reactant and the catalyst were added to cyclohexane at a mass ratio of 1:0.75, and 2-5 MPa of H 2, the hydrocyclization isomerization reaction is carried out in a reactor at 200-300°C. The reaction has no requirements for the reactor, and intermittent reactors, fixed reactors, and fluidized reactors are all acceptable. After the reaction, samples are taken and the components are analyzed using a Shimadzu TQ2010 gas chromatograph-mass spectrometer. The catalyst performance and the selectivity of cycloalkanes and isoalkanes are shown in Table 1;
[0060] Example 2
[0061] The operation steps are the same as those in Example 1, except that in step (1), the raw material in step (1) is changed to chloroplatinic acid (2wt% Pt), and the subsequent steps are performed after impregnation to obtain a 2Pt@MHS-Z5 catalyst with a mass fraction of Pt of 2%, which is named catalyst A2.
[0062] The C10 reactant and the catalyst were added to cyclohexane at a mass ratio of 1:0.75, and 2-5 MPa of H 2 , and the hydrocycloisomerization reaction was carried out in a high-pressure reactor at 200-300°C. After the reaction, samples were taken and the components were analyzed using a Shimadzu TQ2010 gas chromatograph-mass spectrometer. The catalyst performance and the selectivity of cycloalkanes and isoalkanes are shown in Table 1;
[0063] Example 3
[0064] The operation steps are the same as those in Example 1, except that in step (1), the raw material in step (1) is changed to chloroplatinic acid (3wt% Pt), and the subsequent steps are performed after impregnation to obtain a 1Pt@MHS-Z5 catalyst with a mass fraction of Pt of 3%, named catalyst A3.
[0065] The C10 reactant and the catalyst were added to cyclohexane at a mass ratio of 1:0.75, and 2-5 MPa of H 2 , and the hydrocycloisomerization reaction was carried out in a high-pressure reactor at 200-300°C. After the reaction, samples were taken and the components were analyzed using a Shimadzu TQ2010 gas chromatograph-mass spectrometer. The catalyst performance and the selectivity of cycloalkanes and isoalkanes are shown in Table 1;
[0066] Example 4
[0067] The operation steps are the same as those in Example 1, except that in step (1), the raw material in step (1) is changed to chloroplatinic acid (5wt% Pt), and the subsequent steps are performed after impregnation to obtain a 5Pt@MHS-Z5 catalyst with a mass fraction of Pt of 5%, which is named catalyst A4.
[0068] The C10 reactant and the catalyst were added to cyclohexane at a mass ratio of 1:0.75, and 2-5 MPa of H 2, and the hydrocycloisomerization reaction was carried out in a high-pressure reactor at 200-300°C. After the reaction, samples were taken and the components were analyzed using a Shimadzu TQ2010 gas chromatograph-mass spectrometer. The catalyst performance and the selectivity of cycloalkanes and isoalkanes are shown in Table 1;
[0069] Example 5
[0070] The operation steps are the same as those in Example 1, except that in step (1), the raw material in step (1) is changed to nickel nitrate (3 wt % Ni), and the subsequent steps are performed after impregnation. 2 The reduction catalyst temperature was adjusted to 500°C to obtain a 3Ni@MHS-Z5 catalyst with a Ni mass fraction of 3%, which was named catalyst B1.
[0071] The C10 reactant and the catalyst were added to cyclohexane at a mass ratio of 1:0.75, and 2-5 MPa of H 2 , and the hydrocycloisomerization reaction was carried out in a high-pressure reactor at 200-300°C. After the reaction, samples were taken and the components were analyzed using a Shimadzu TQ2010 gas chromatograph-mass spectrometer. The catalyst performance and the selectivity of cycloalkanes and isoalkanes are shown in Table 1;
[0072] Example 6
[0073] The operation steps are the same as those in Example 1, except that in step (1), the raw materials in step (1) are changed to chloroplatinic acid (1wt% Pt) and nickel nitrate (2wt% Ni), and the subsequent steps are performed after impregnation. 2 The reduction catalyst temperature was adjusted to 500° C. to obtain a 2Ni1Pt@MHS-Z5 catalyst having a Ni mass fraction of 2% and a Pt mass fraction of 1%, which was named catalyst B2.
[0074] The C10 reactant and the catalyst were added to cyclohexane at a mass ratio of 1:0.75, and 2-5 MPa of H 2 , and the hydrocycloisomerization reaction was carried out in a high-pressure reactor at 200-300°C. After the reaction, samples were taken and the components were analyzed using a Shimadzu TQ2010 gas chromatograph-mass spectrometer. The catalyst performance and the selectivity of cycloalkanes and isoalkanes are shown in Table 1;
[0075] Example 7
[0076] The operation steps are the same as those in Example 1, except that in step (1), the raw materials in step (1) are changed to chloroplatinic acid (1.5wt% Pt) and nickel nitrate (1.5wt% Ni), and the subsequent steps are performed after impregnation. 2The reduction catalyst temperature was adjusted to 500° C. to obtain a 1.5Ni1.5Pt@MHS-Z5 catalyst having a Ni mass fraction of 1.5% and a Pt mass fraction of 1.5%, which was named catalyst B3.
[0077] The C10 reactant and the catalyst were added to cyclohexane at a mass ratio of 1:0.75, and 2-5 MPa of H 2 , and the hydrocycloisomerization reaction was carried out in a high-pressure reactor at 200-300°C. After the reaction, samples were taken and the components were analyzed using a Shimadzu TQ2010 gas chromatograph-mass spectrometer. The catalyst performance and the selectivity of cycloalkanes and isoalkanes are shown in Table 1;
[0078] Example 8
[0079] The operation steps are the same as those in Example 1, except that in step (1), the raw materials in step (1) are changed to chloroplatinic acid (2wt% Pt) and nickel nitrate (1wt% Ni), and the subsequent steps are performed after impregnation. 2 The reduction catalyst temperature was adjusted to 500° C. to obtain a 1Ni2Pt@MHS-Z5 catalyst having a Ni mass fraction of 1% and a Pt mass fraction of 2%, which was named catalyst B4.
[0080] The C10 reactant and the catalyst were added to cyclohexane at a mass ratio of 1:0.75, and 2-5 MPa of H 2 , and the hydrocycloisomerization reaction was carried out in a high-pressure reactor at 200-300°C. After the reaction, samples were taken and the components were analyzed using a Shimadzu TQ2010 gas chromatograph-mass spectrometer. The catalyst performance and the selectivity of cycloalkanes and isoalkanes are shown in Table 1;
[0081] Example 9
[0082] The operation steps are the same as those in Example 1, except that in step (1), the raw materials in step (1) are changed to ferric nitrate (1wt% Fe) and chloroplatinic acid (2wt% Pt), and the subsequent steps are performed after impregnation. 2 The reduction temperature of the catalyst was adjusted to 500°C to obtain a 1Fe2Pt@MHS-Z5 catalyst with a Pt mass fraction of 3%, which was named catalyst C1.
[0083] The C10 reactant and the catalyst were added to cyclohexane at a mass ratio of 1:0.75, and 2-5 MPa of H 2 , and the hydrocycloisomerization reaction was carried out in a high-pressure reactor at 200-300°C. After the reaction, samples were taken and the components were analyzed using a Shimadzu TQ2010 gas chromatograph-mass spectrometer. The catalyst performance and the selectivity of cycloalkanes and isoalkanes are shown in Table 1;
[0084] Example 10
[0085] The operation steps are the same as those in Example 1, except that in step (1), the raw materials in step (1) are changed to ferric nitrate (2wt% Fe) and chloroplatinic acid (1wt% Pt), and the subsequent steps are performed after impregnation. 2 The reduction catalyst temperature was adjusted to 500° C. to obtain a 2Fe1Pt@MHS-Z5 catalyst having a Fe mass fraction of 2% and a Pt mass fraction of 2%, which was named catalyst C2.
[0086] The C10 reactant and the catalyst were added to cyclohexane at a mass ratio of 1:0.75, and 2-5 MPa of H 2 , and the hydrocycloisomerization reaction was carried out in a high-pressure reactor at 200-300°C. After the reaction, samples were taken and the components were analyzed using a Shimadzu TQ2010 gas chromatograph-mass spectrometer. The catalyst performance and the selectivity of cycloalkanes and isoalkanes are shown in Table 1;
[0087] Embodiment 11
[0088] The operation steps are the same as those in Example 1, except that in step (1), the raw materials in step (1) are changed to ferric nitrate (1wt% Fe), chloroplatinic acid (1wt% Pt), and nickel nitrate (1wt% Ni), and the subsequent steps are performed after impregnation. 2 The reduction catalyst temperature was adjusted to 500° C. to obtain a 1Fe1Ni1Pt@MHS-Z5 catalyst having a mass fraction of 1% Fe, 1% Ni, and 1% Pt, which was named catalyst C3.
[0089] The C10 reactant and the catalyst were added to cyclohexane at a mass ratio of 1:0.75, and 2-5 MPa of H 2 , and the hydrocycloisomerization reaction was carried out in a high-pressure reactor at 200-300°C. After the reaction, samples were taken and the components were analyzed using a Shimadzu TQ2010 gas chromatograph-mass spectrometer. The catalyst performance and the selectivity of cycloalkanes and isoalkanes are shown in Table 1;
[0090] Comparative Example 1
[0091] Pt / NbOPO4 has good performance in hydrogenation and is used as a comparative example of the present invention. The synthesis method thereof is as follows:
[0092] (1) Dissolve 1.32 g of diammonium hydrogen phosphate in 20 ml of water, and then adjust the pH to 2 with phosphoric acid. Add 20 ml of 0.M niobium oxalate (pH = 2) to the above solution under vigorous stirring;
[0093] (2) Dissolve 1.0 g of hexadecyltrimethylammonium bromide (CTAB) in 15 mL of distilled water, and then add the mixed solution dropwise to the CTAB aqueous solution. The pH value of the final solution is about 2;
[0094] (3) Stir at 35°C for 60 minutes, then age the solution in a Teflon-lined autoclave at 160°C for 24 hours. After cooling, the solid was filtered, washed with distilled water, and then dried at 50°C overnight. Calcinate at 500°C for 5 hours;
[0095] (4) After impregnation with Pt salt (3% wt), the mixture was dried at 100°C for 12 h and calcined at 500°C for 3 h to obtain the hydrogenation catalyst PtO 2 / NbOPO4
[0096] (5) At 350°C, 5% H 2 / Ar environment, the PtO in step (4) 2 / NbOPO4 was reduced for 4 h to obtain the hydrogenation catalyst Pt / NbOPO4, which was named catalyst D.
[0097] The C10 reactant and the catalyst were added to cyclohexane at a mass ratio of 1:0.75, and 2-5 MPa of H 2 The hydrocycloisomerization reaction was carried out in a high pressure reactor at 200-300°C. After the reaction, samples were taken and the components were analyzed by Shimadzu TQ2010 gas chromatography-mass spectrometry. The catalyst performance and the selectivity of cycloalkanes and isoalkanes are shown in Table 1.
[0098] Table 1 Components of the catalysts of Examples 1 to 11 and the products of Comparative Example 1 after the reaction
[0099]
[0100] Examples 1-4 are to coat different amounts of Pt metal inside the hierarchical pore ZSM-5 to explore the effect of the amount of Pt metal loaded on the hydrogenation of the C10 precursor. Figure 1The results of hydrogenation of the four catalyst groups A1, A2, A3, and A4 in Table 1 are shown. Among them, the A3 catalyst with a Pt loading of 3% obtained the highest alkane yield, and the precursor was completely hydrogenated to generate alkanes. At low loadings, low alkane yields appeared in the catalytic results of the A1 and A2 catalysts, and the components that were not completely converted into alkanes in the products were characterized by a large number of undeoxygenated and unhydrogenated products and a large number of C=C unsaturated products. In the deoxygenation and hydrogenation reaction, the precious metal Pt can not only provide activated hydrogen atoms for saturating unsaturated double bonds, but also synergize with B acid to remove oxygen from the precursor. In the A1 group, the Pt loading was too low, and poor activity was shown in both deoxygenation and hydrogenation reactions. The A2 loading was further increased, and all products were deoxygenated, but there were a large number of unsaturated C=C bonds. It shows that the catalyst has good activity for deoxygenation reaction, but poor hydrogen activation ability, and cannot be hydrogenated well. The A3 catalyst showed good deoxygenation and hydrogenation performance, achieving complete conversion of the precursor material and a 30% yield of high-value cycloalkanes. The A4 catalyst after further increasing the Pt loading did not perform as expected, and the catalytic activity decreased significantly. This is related to the fact that after high loading, the metal easily forms large metal clusters during calcination, and the poor dispersion leads to a decrease in activity. Figure 2 This is a TEM image of the A4 catalyst after transmission electron microscopy characterization. It can be seen that a large number of Pt clusters on the catalyst, with poor dispersion and unable to effectively provide metal active sites. The experimental results show that the A3 catalyst has a suitable loading amount, which can not only cooperate with B acid to complete the deoxygenation reaction, but also provide activated hydrogen well to promote the hydrogenation reaction and obtain a high cycloalkane yield. However, the catalyst also has obvious defects: the loaded single metal Pt is prone to agglomeration, and due to the high price of Pt, the catalyst cost is relatively high. The introduction of some transition metals in appropriate amounts can improve this problem.
[0101] Examples 5-8 are hydrogenation results of introducing transition metal Ni to gradually or completely replace Pt in the catalyst of Example 3, with the total metal loading being kept constant at 3%. In Examples 5-8, the loading of Ni is successively reduced to 3%, 2%, 1.5%, and 1%, respectively. Figure 3 The following is a comparison of the hydrogenation results after the introduction of Ni. In Example 5, the B1 catalyst is loaded with 3% pure Ni. Ni's ability to activate hydrogen is much weaker than Pt, and usually it has a better effect above 5%, so the catalytic effect of B1 is very poor. In Examples 6-8, by adjusting different Ni-Pt ratios, good catalytic effects were shown. Among them, Example 6, which loaded the B2 catalyst with 1% Pt and 2% Ni, achieved the best effect. After the introduction of Ni, not only the dispersibility of Pt was changed, so that Pt could fully activate hydrogen, but also the B / L acid ratio in the catalyst was changed. After the introduction of nickel, the B / L in the catalyst will decrease, so the selectivity for cycloalkanes will also decrease significantly, but the excellent isomerization ability is still retained. Figure 4 The powder diffraction characterization of the catalysts used in Examples 5-8 shows that when only Ni is loaded, a diffraction peak of Ni appears at 43.1°, and a metal peak appears at a low loading, indicating that Ni forms metal particles of >4nm. In the powder diffraction patterns of B3 and B4 catalysts with Pt loadings of 1.5% and 2%, a Pt peak appears at 39.5°, while in the test results of B2 catalyst, neither Pt nor Ni peaks appear, indicating that the metal dispersion is uniform, which is the reason why Example 6 has the best result. Figure 5 This is the transmission electron microscope and energy spectrum scan of the B2 catalyst. Among them, the metal particles are small in size and are mainly Ni particles, and the Pt particles are evenly distributed in the catalyst. The B2 catalyst has good isomerization ability and the Pt metal is evenly dispersed, but because its B / L acid is still large, it causes excessive breakage of the carbon chain and generates 9.5% of alkanes other than C8-C16 aviation kerosene. Further introduce other metals, change the B / L acid, and observe the catalytic activity of different metals.
[0102] In Examples 9-11, different amounts of Fe were introduced into the catalysts. Under the premise of a total metal loading of 3%, the active metal components of the C1, C2, and C3 catalysts were 1% Fe2% Pt, 2% Fe1% Pt, and 1% Fe1% Ni1% Pt, respectively. Figure 6 The results of hydrogenation of Examples 9 to 11 are compared. When only Fe and Pt are loaded, the catalytic effect is poor, and the alkane yields are 14% and 32% respectively. The components of the product components that are not deoxygenated and hydrogenated are mainly undeoxygenated unsaturated products and undeoxygenated products. Figure 7 The following is the powder diffraction characterization (XRD) of catalysts C1, C2, and C3. When loaded with 1% Fe2% Pt, no Fe peak appeared in the XRD, and a large bulge appeared near 39.5, which corresponds to the Pt peak. The flattened peak indicates that Pt is agglomerated into particles, but the size is small, and it is likely that it forms alloy agglomerates with Fe. Poor dispersibility leads to a large number of undeoxidized and unhydrogenated products in Example 9. The Fe element has a poor ability to activate hydrogen. Compared with 2% Ni1% Pt in Example 6, the activity of 2% Fe1% Pt for hydrogenation reactions is significantly reduced. The C3 catalyst retains the high activity of the B2 catalyst and further reduces the B / L, thereby producing less non-jet fuel components C8-C16. Figure 8 This is the transmission electron microscope and energy spectrum scan of the C3 catalyst. After introducing 1% Fe to replace 1% Ni, the three metals have good dispersion and are evenly distributed in the catalyst.
[0103] Table 2 Infrared test results of catalyst pyridine in Examples 3, 6, 11 and Comparative Example 1
[0104]
[0105] Comparative Example 1 is a catalyst with excellent effect currently developed. Hydrogenation is carried out under the same conditions, and A3, B2, and C3 with good working effect of the present invention are compared. Table 2 is the infrared and BET test results of pyridine of A3, B2, C3 and D. After the introduction of other metals, B / L acid is significantly reduced. Compared with the D catalyst, the catalyst developed by the present invention has a super large specific surface area, which is conducive to the mass transfer problem in the reaction process. A3, B2, and C3 catalysts are metal-coated inside ZSM-5, which has a stronger confinement effect on the metal compared with the D catalyst, and can ensure a longer service life of the catalyst. Fig. 9 The hydrogenation products of Examples 3, 6, and 11 are compared with those of Comparative Example 1. Fig. 9 The distribution of components in the products after catalysis by three example catalysts A3, B2, and C3 and comparative catalyst D was compared. Compared with the hydrogenation results of Pt / NbOPO4 with excellent hydrogenation ability, the three metal-coated hollow multi-level pore ZSM-5 catalysts prepared by the present invention have good cycloisomerization ability. After the reaction, the selectivity of isomerized cycloalkanes is 56% to 67%, which is significantly higher than the sum of isoalkanes and cycloalkanes in the hydrogenation results of Pt / NbOPO4, which is 30.6%. Highly selective preparation of isoalkanes and cycloalkanes was achieved at a relatively low temperature.
[0106] It can be seen from the data in Table 1 that the metal-coated multi-level porous ZSM-5 catalyst prepared according to the present invention with hollow multi-level porous ZSM-5 as the carrier and active metal components of 1 to 3 kinds of Fe, Ni and Pt for the cycloisomerization of long straight-chain alkanes of aviation kerosene (the contents of the three active components are 1-3wt% of Fe, 1-3wt% of Ni and 1-3wt% of Pt, respectively) has high isomerization activity and cyclization ability, good catalytic stability, and low reaction temperature, and the reaction temperature is low, and the cycloisomerization activity of long-chain alkanes of aviation kerosene can be maintained at a relatively low temperature.
[0107] Example 12
[0108] (1) Calculated amounts of chloroplatinic acid (5 wt% Pt), nickel nitrate (5 wt% Ni) and ferric nitrate (5 wt% Fe) were dissolved in deionized water and added to commercially purchased H-type ZSM-5;
[0109] (2) The mixture was stirred vigorously, stirred at room temperature for 10 h, and then impregnated into a ZSM-5 support;
[0110] (3) The impregnated material in step (2) was dried at 80°C and calcined at 550°C for 6 hours to obtain a supported catalyst PtO 2 NiOFe 2 O 3 / ZSM-5;
[0111] The impregnated metal salts are decomposed by calcination. Under common atmospheric conditions, nickel salts decompose at 170-300°C, iron salts decompose at 150-350°C, and platinum salts decompose at 200-400°C.
[0112] (4) Add the calculated amount of TPAOH (25 wt%):NaOH mixed solution with a molar ratio of 1:1 to the PtO prepared in step (3) 2 NiOFe 2 O 3 / ZSM-5, after stirring, hydrothermally heated in an oven at 200°C for 48 hours, centrifuged and dried at 120°C for 12 hours, calcined at 500°C for 8 hours, with a heating rate of 4°C / min, to obtain a sodium-type metal oxide-coated hierarchical porous catalyst PtO 2 NiOFe 2 O 3 @Na-MHS-Z5;
[0113] Calcination is mainly for the decomposition of tetrapropylammonium hydroxide, and the main temperature range for the decomposition of tetrapropylammonium hydroxide is 250-350°C. The calcination temperature is usually 500-600°C, and sometimes it is increased to 550-650°C depending on the specific type of molecular sieve. In this temperature range, not only the template is completely decomposed and burned, but also the molecular sieve framework can be stabilized.
[0114] (5) PtO obtained in step (4) 2 NiOFe 2 O 3 @Na-MHS-Z5 powder was dispersed in a 0.5 mol / L aqueous solution of ammonium chloride, and ion exchange was carried out at 60°C with vigorous stirring for 4 h, and repeated twice; dried at 60°C for 12 h, and calcined at 600°C for 4 h to obtain H-type PtO 2 NiOFe 2 O 3 @MHS-Z5;
[0115] (6) At 500°C, 5% H 2 / Ar environment to remove the PtO in step (5) 2 NiOFe 2 O 3 @MHS-Z5 is reduced to obtain the reduced cycloisomerization catalyst PtNiFe@MHS-Z5, wherein the mass fractions of the active metals Pt, Ni, and Fe are all 5%.
[0116] Embodiment 13
[0117] (1) Calculated amounts of chloroplatinic acid (3 wt% Pt), nickel nitrate (3 wt% Ni) and ferric nitrate (3 wt% Fe) were dissolved in deionized water and added to commercially purchased H-type ZSM-5;
[0118] (2) The mixture was stirred vigorously, stirred at room temperature for 3 h, and then impregnated into a ZSM-5 support;
[0119] (3) The impregnated material in step (2) was dried at 120°C and calcined at 400°C for 6 hours to obtain a supported catalyst PtO 2 NiOFe 2 O 3 / ZSM-5;
[0120] (4) Add the calculated amount of TPAOH (25 wt%):NaOH mixed solution with a molar ratio of 1:12 to the PtO prepared in step (3) 2 NiOFe 2 O 3 / ZSM-5, after stirring, hydrothermally heated in an oven at 110°C for 96 hours, dried at 60°C for 24 hours after centrifugation, calcined at 700°C for 4 hours, and heated at a rate of 10°C / min to obtain a sodium-type metal oxide-coated multi-level porous catalyst PtO 2 NiOFe 2 O 3 @Na-MHS-Z5;
[0121] (5) PtO obtained in step (4) 2 NiOFe 2 O 3 @Na-MHS-Z5 powder was dispersed in a 2 mol / L aqueous solution of ammonium chloride, and ion exchange was carried out at 60 °C with vigorous stirring for 2 h, and repeated 3 times; dried at 100 °C for 12 h, and calcined at 300 °C for 7 h to obtain H-type PtO 2 NiOFe 2 O 3 @MHS-Z5;
[0122] (6) At 500°C, 5% H 2 / Ar environment to remove the PtO in step (5) 2 NiOFe 2 O 3 @MHS-Z5 was reduced to obtain the reduced cycloisomerization catalyst PtNiFe@MHS-Z5, wherein the mass fractions of the active metals Pt, Ni, and Fe were all 3%.
[0123] In Example 13, due to the large metal loading, metal particles with large particle size are formed. Although this greatly reduces the utilization rate of metal active sites, due to the large number of metal active components, there is still a certain deoxidation and hydrogenation capacity. More than 30% of the substances in the product are difficult to fully saturate the C=C and C=O bonds therein, which is related to the decrease in metal site utilization. In Example 12, the active metal components of Pt, Fe, and Ni encapsulated in the multi-level pore ZSM-5 are all 5%, with the highest metal loading, and the total metal loading reaches 15%. The metal particle size formed is the largest, and some large metal blocks fall off from the carrier. The oversized metal blocks reduce the efficiency of metal activation hydrogen, and the excessive metal loading significantly increases the L acid amount of the catalyst, while the B acid amount significantly decreases. The B / L acid ratio is too low and the deoxidation function cannot be achieved. In the obtained product, not only a large number of products do not have saturated double bonds, but also a large number of oxygen-containing substances, and the overall yield of alkanes is less than 10%. This shows that the appropriate metal ratio composition has a very large impact on the activity, selectivity and structure of the catalyst.
[0124] The present invention has been described above in the form of specific embodiments. Those skilled in the art should understand that the present disclosure is not limited to the embodiments described above, and various changes, modifications and substitutions may be made without departing from the scope of the present invention.
Claims
1. A metal-coated multi-level porous ZSM-5 catalyst for the hydrocycloisomerization of aviation kerosene carbon chain precursors, characterized in that: The invention is composed of a multi-level pore hollow ZSM-5 carrier and one or more metal components of Fe, Ni or Pt, wherein the metal is coated inside the ZSM-5 carrier; the contents of the metal components are 1 to 5 wt% Ni, 1 to 5 wt% Fe, and 1 to 5 wt% Pt respectively; the specific surface area of the multi-level pore hollow ZSM-5 carrier is 402 to 440 m 2 / g, the pore volume is 0.43~0.21ml / g, and the B acidity is 12~26mmol / g.
2. The metal-coated multi-level porous ZSM-5 catalyst according to claim 1, characterized in that: The metal components are preferably 1 wt% Ni, 1 wt% Fe, and 1 wt% Pt.
3. The metal-coated multi-level porous ZSM-5 catalyst according to claim 1, characterized in that: It is used for the hydrogenation cycloisomerization of aviation kerosene carbon chain precursor containing 10 to 15 carbon atoms, specifically: adding aviation kerosene carbon chain precursor and metal-coated multi-level porous ZSM-5 in a mass ratio of 1:0.75 into cyclohexane, introducing 2 to 5 MPa of H2, and carrying out catalytic reaction in a high-pressure reactor at 200 to 300°C; the obtained product contains 30 to 50% of cycloalkanes or isoalkanes, and the total of cycloalkanes and isoalkanes is 50 to 70%.
4. A method for preparing a metal-coated multi-level porous ZSM-5 catalyst for hydrogenation cycloisomerization of aviation kerosene carbon chain precursors, characterized in that: The following steps are included: Step 1, dissolving one or two or more of an iron salt, a platinum salt and a nickel salt in deionized water in proportion to obtain a mixed solution A; The mass fraction of Fe in the iron salt is 1 to 5 wt %, the mass fraction of Pt in the platinum salt is 1 to 5 wt %, the mass fraction of Ni in the nickel salt is 1 to 5 wt %, and the rest is deionized water; Step 2: Add the mixed solution A to the H-type ZSM-5, add a magnet, and stir vigorously on a magnetic stirrer until the compound is fully impregnated into the ZSM-5 carrier; The immersion time is 3 to 10 hours; Step 3, drying and calcining the impregnated material to obtain supported metal oxide / ZSM-5; Step 4, adding tetrapropylammonium hydroxide and sodium hydroxide solution to the supported metal oxide / ZSM-5, stirring, hydrothermal, centrifuging, drying, and calcining to obtain a sodium-type metal oxide-coated multi-level porous catalyst metal oxide@MHS-Z5; The mass fraction of tetrapropylammonium hydroxide is 25wt%, and the molar ratio of tetrapropylammonium hydroxide to sodium hydroxide is 1 to 12:1; Step 5, dispersing the metal oxide @MHS-Z5 powder in an aqueous solution of ammonium chloride, stirring to perform ion exchange, drying and calcining to obtain H-type metal oxide @MHS-Z5; Each gram of metal oxide @MHS-Z5 powder is added to 30-60 ml of ammonium chloride solution; Step six, reducing the H-type metal oxide @MHS-Z5 in a H2 / Ar environment at 300°C to 500°C to obtain the reduced metal @MHS-Z5.
5. The preparation method according to claim 4, characterized in that: The nickel salt is one of nickel nitrate, nickel acetate and nickel chloride, or a combination of two or more thereof; the iron salt is one of iron nitrate, iron chloride, iron nitrate, iron oxalate and iron acetate, or a combination of two or more thereof; the platinum salt is one of platinum chloride, chloroplatinic acid and platinum nitrate, or a combination of two or more thereof.
6. The preparation method according to claim 4, characterized in that: The preferred time for the immersion is 5 to 8 hours.
7. The preparation method according to claim 4, characterized in that: The calcination temperature in step 3 is 400-550° C. and the calcination time is 6 hours to decompose the metal salt in the impregnated material.
8. The preparation method according to claim 4, characterized in that: The hydrothermal reaction temperature in step 4 is 110-200°C for 48-96h; the filter cake drying temperature is 60-120°C; the calcination temperature is 500-700°C, the heating rate is 4-10°C / min, and the calcination time is 4-8h, so that the tetrapropylammonium hydroxide is decomposed and the molecular sieve framework is stabilized.
9. The preparation method according to claim 4, characterized in that: The ion exchange in step 5 is repeated 2 to 3 times; the drying temperature is 60 to 100° C., the calcination temperature is 300 to 600° C., and the calcination time is 4 to 7 hours.
Citation Information
Patent Citations
Preparation method of aviation kerosene or diesel oil scope liquid alkane
CN104711007A
Catalyst for efficient pyrolysis heterogeneous one-step preparation of short-chain isoparaffin, and preparation method and application of catalyst
CN110743608A
Preparation method of shape-selective isomerization catalyst based on MFI type structure molecular sieve
CN111229296A
Application of hierarchical pore molecular sieve in preparation process of cyclopentadiene and JP-10 aviation fuel
CN113045392A
Bimetal supported catalyst, preparation method thereof and application of bimetal supported catalyst in preparation of biological aviation kerosene through hydrogenation conversion of palm oil
CN114522716A